How well can smallholders in the Amazon live: an analysis of livelihoods and forest conservation in cacao- and cattle-based farms in the Eastern Amazon, Brazil - Braga, Daniel Palma Perez (2019)
Since the first colonists were settled along the Transamazon highway in Eastern Brazilian Amazon, in the early 1970s, it has been hotly debated how to guarantee their livelihoods. Over time, cattle ranching became the priority option. However, with increasing awareness about the socio- environmental drawbacks of this production system, the search for less damaging production systems was intensified. Cacao (Theobroma cacao L.) based agroforestry systems present one of the most promising land use options because they conciliate attractive yields with ecosystems conservation. Independent from this, many smallholders (small-scale households) continue seeing cattle ranching as their dedication. Whether and to what degree, these perceptions and expectations are realistic is not known, as most studies concentrate on technical aspects so far. Against this backdrop, this study invested in better understanding what small-scale farmers dedicated to cacao and/or cattle can realistically expect regarding living standard of their family and the forest conservation as stability of their natural production basis. Along seven municipalities, we applied structured interviews to 95 households. As suggested by Principal Component Analysis, we used the responses about income and housing to define the economic well-being and calculate success levels for each household. We then calculated correlations and frequencies, and applied hypotheses tests (Spearman and Kruskall-Wallis). The data showed for nearly two thirds of the visited families an acceptable to good living standard (with an average income higher than 17,000 USD/year), but also, concerning weaknesses for the rest. The most relevant factors, positively related to success, were land size and level of technology. For successful households, the combination of social interactions, market niches and off-farm income showed relevancy. Cacao farmers could be as successful as cattle ranchers, regarding cacao (on suitable soils) generated at least six times higher income per hectare than cattle. When households adopted both systems the chances of success were even higher, but on the cost of more deforestation. With regards to forest conservation, agroforestry systems related to a diversification of the household economic basis, at best including the use of non-timber products of native trees, could be feasible alternatives for extensive cattle ranching. However, to diffuse such more complex production systems requires better policies and effective support grounded in a thorough institutional cooperation of multilateral stakeholders able to establish effective logistics and attractive markets for the related diverse array of products. Further studies should increase focus on the aspects of context and personal pathways of households, using complimentary descriptive methods beyond just quantitative evaluations.